Kinematics and structure of star-forming regions: insights from cold collapse models - Kuznetsova, Aleksandra; Hartmann, Lee; Ballesteros-Paredes, Javier (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. The origin of the observed morphological and kinematic substructure of young star-forming regions is a matter of debate. We offer a new analysis of d